Monitoring Pembangkit Listrik Tenaga Surya Berbasis Arduino dengan Media Telegram - Tamam, M. Taufiq; Aditia, M. Indra (Proceedings Series on Physical & Formal Sciences, 2023)
The implementation of monitoring the performance parameters of the PLTS system in several regions is still done manually so that the data obtained is also limited. In this study the PLTS monitoring system is based on Arduino Uno so that monitoring on PLTS can be monitored with telegram media. The monitoring system has two inputs, namely for PV and for the battery. To monitor the value of the electrical energy parameter, the INA219 sensor is used. The sensor reading results are displayed on the 16x2 LCD and mobile phone by sending the "STATUS" message command to the ESP8266 wifi module. Retrieval of current and voltage data on INA219 sensor readings and standard measuring instruments is carried out every 5 minutes. The system can monitor via an Android smartphone using Telegram. The test results show that the Telegram application can display and monitor photovoltaic and batteries in real time. The average error during sensor monitoring at photovoltaic output is 0.16% for voltage and 1.25% for current. The sensor reading results have an average error when charging the battery of 1.36% for voltage and 2.04% for current. The characteristics of the results of this measurement meet the requirements of IEC standard no. 13B-23.